PENGARUHSELF-EFFICACY, MOTIVASI KERJA, DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada UMKM Batik Gayatri Desa Polandak Kecamatan Pancur Kabupaten Rembang - Intan Cahya Bahari, 14.05.51.0177; Rahayuningsih, Sri (Students' Journal of Economic and Management, 2018)
ABSTRACT This research takes object at UMKM Batik Gayatri Polandak village Pancur district Rembang district. The purpose of this study is to examine and analyze the influence of self-efficacy, work motivation, and job training on work productivity of UMKM Batik Gayatri village Pancur district Rembang district.Population in this reseacrh is all employess at UMKM Batik Gayatri Polandak village Pancur district Rembang district numbering 150. The sampling technique used purposive sampling with 130 respondents. The methode of data anaylisis is validity test, reliability test, coefficent of determination, test f, multipleregression analysis and hypotesis testing troughtt-test.The result showed that, self-efficacy have positive and significant impact on work productivity, work motivation have positive and significant impact on work productivity, and job training have positive and significant impact on work productivity. Keywords : self-efficacy, work motivation, on job training and work productivity